A risk-based pesticide residue monitoring tool to prioritize the sampling of fresh produce. (April 2015) - Delcour, Ilse; Rademaker, Michael; Jacxsens, Liesbeth; De Win, Jessie; De Baets, Bernard; Spanoghe, Pieter
Abstract: Pesticide residues remain a key issue in food safety for consumers. Accordingly, pesticide residue monitoring at all stages of the food chain gains importance. In Europe, fresh produce processing and trading companies are requested to have a company-specific sampling plan that covers all on-site food safety risk issues. In settings where the prevalence of contamination is known and there are a limited number of suppliers, statistical sampling plans are easily designed based on theoretical calculations. Unfortunately, this is not the case in the current setting of fresh produce. In order to provide a workable alternative, empirical guidelines for the design of a risk-based sampling plan, applicable in a broad range of realistic scenarios, are established. These guidelines are based on the opinions of experts regarding the relative importance with respect to risk regarding five criteria related to products and suppliers. These criteria are: supplier guarantee, country of origin, cross-contamination, and processing and product risk. The opinions of the experts are aggregated in order to yield a weighted-sum-based risk indicator. This can facilitate the risk assessment of new scenarios and sample size calculations. While these guidelines for the design of a risk-based sampling plan do not provide guarantees for a statistically demonstrated level of safety, the plan has been proven to be a useable tool during validation. Finally, the use of this tool is demonstrated in a case study. Highlights: We deal with fresh produce sampling in a multi-commodity multi-producer setting. We provide a tool to facilitate product risk assessment, based on experts' opinions. These opinions are based on descriptive objective parameters. Experts' opinions are closely approximated by the resulting tool. A realistic example use of the product risk tool is provided.